The Analisis Celah Keamanan Website Poltekkes Kemenkes Sorong Menggunakan Metode Penetration Testing - Gunawan Yudi Jayanto; Julius Panda Putra Naibaho; Alex De Kweldju (SMATIKA JURNAL : STIKI Informatika Jurnal, 2025)
Currently, information technology is very necessary, in the digital era cybersecurity is one of the main factors for an institution to survive and be recognized for its credibility, including educational institutions, the Poltekkes Sorong Website is used as the main portal or media to disseminate academic information, interaction between students and the public, However, the existence of security gaps is something that allows cyber attacks to be carried out which can endanger data confidentiality. This study aims to analyze the security gaps in the Poltekkes Kemenkes Sorong website, the testing carried out using the penetration testing method which has several stages including collecting scanning information, vulnerability analysis. So that this study can provide guidance and practice for information system managers at Poltekkes Kemenkes Sorong to reduce the risk of cyber attacks and protect sensitive data held by the institution.